2016
DOI: 10.3847/0004-637x/820/2/98
|View full text |Cite
|
Sign up to set email alerts
|

Young Galaxy Candidates in the Hubble Frontier Fields. Iii. MACS J0717.5+3745

Abstract: In this paper we present the results of our search for and study of z 6 galaxy candidates behind the third Frontier Fields (FF) cluster, MACSJ0717.5+3745, and its parallel field, combining data from Hubble and Spitzer. We select 39 candidates using the Lyman Break technique, for which the clear non-detection in optical make the extreme mid-z interlopers hypothesis unlikely. We also take benefit from z 6 samples selected using previous Frontier Fields datasets of Abell 2744 and MACS0416 to improve the constrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
63
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 132 publications
(264 reference statements)
11
63
2
Order By: Relevance
“…Small differences in the assumed half-light radii have the potential to change the inferred faintend slopes by large factors, i.e., 0.3  a D depending on whether the mean size of extremely faint galaxies is 120 mas, 30 mas, or 7.5 mas (e.g., see Figure 2 from Bouwens et al 2017). Fortunately, we found that most of the extremely faint sources seem consistent with being almost unresolved, i.e., with intrinsic sizes of <10-30 mas (Bouwens et al 2017; see also Kawamata et al 2015;Laporte et al 2016), making this issue much more manageable in terms of its impact; but it still remains an uncertainty. A second source of systematic error arises from errors in the magnification maps, since this can have a profound impact on the LFs derived.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Small differences in the assumed half-light radii have the potential to change the inferred faintend slopes by large factors, i.e., 0.3  a D depending on whether the mean size of extremely faint galaxies is 120 mas, 30 mas, or 7.5 mas (e.g., see Figure 2 from Bouwens et al 2017). Fortunately, we found that most of the extremely faint sources seem consistent with being almost unresolved, i.e., with intrinsic sizes of <10-30 mas (Bouwens et al 2017; see also Kawamata et al 2015;Laporte et al 2016), making this issue much more manageable in terms of its impact; but it still remains an uncertainty. A second source of systematic error arises from errors in the magnification maps, since this can have a profound impact on the LFs derived.…”
Section: Introductionmentioning
confidence: 52%
“…Based on recent results from a number of papers (Bouwens et al 2017; see also Laporte et al 2016), it is now clear that the use of such large sizes for very faint galaxies is not realistic. Several lines of evidence indicate that the intrinsic half-light radii of very low luminosity sources (i.e., 16 mag >-) are very small, i.e., 0 03, with many sources appearing to have sizes 0 01 (Bouwens et al 2017).…”
Section: L17mentioning
confidence: 99%
See 1 more Smart Citation
“…The HFF project has been remarkably prolific, with contributions in the structure of galaxy clusters (Jauzac et al 2014;Richard et al 2014;Ogrean et al 2015;Jauzac et al 2015), individual high redshift galaxies (McLeod et al 2015;Kawamata et al 2015;Laporte et al 2016), and high redshift galaxy luminosity function and its evolution (Finkelstein et al 2015;Coe et al 2015;Atek et al 2015) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…As of 2016 there are now ∼1000 candidate objects, encompassing a wide range of luminosities, identified (e.g. Bouwens et al 2010Bouwens et al , 2011Bouwens et al , 2014aBouwens et al ,b, 2015aOesch et al 2010Oesch et al , 2013Oesch et al , 2014Oesch et al , 2015Oesch et al , 2016Bunker et al 2010;Wilkins et al 2010Wilkins et al , 2011aFinkelstein et al 2010Finkelstein et al , 2012Finkelstein et al , 2015Lorenzoni et al 2011Lorenzoni et al , 2013McLure et al 2011McLure et al , 2013Ellis et al 2013;Laporte et al 2014Laporte et al , 2015Laporte et al , 2016Schmidt et al 2014;McLeod et al 2015;McLeod, McLure & Dunlop 2016;Atek et al 2015a, Atek et al2015b) with the first small samples now identified at z ∼ 10 and beyond.…”
Section: Introductionmentioning
confidence: 99%